Teaching computer-based spelling to individuals with developmental and hearing disabilities: transfer of stimulus control to writing tasks. - Stromer, Robert; Mackay, Harry A.; Howell, Sarah R. (Journal of Applied Behavior Analysis)
Computer-based instruction may yield widely useful handwritten spelling. Illustrative cases involved individuals with mental retardation and hearing impairments. The participant in Study 1 matched computer pictures and printed words to one another but did not spell the words to pictures. Spelling was then taught using a computerized procedure. In general, increases in the accuracy of computer spelling were accompanied by improvements in written spelling to pictures. Study 2 extended these results with a 2nd participant. After initial training, spelling improved in the context of a retrieval task in which the participant (a) wrote a list of the names of objects displayed on a table, (b) selected the objects from a shelf, and (c) returned the objects to the table. Nearly perfect accuracy scores declined on some retrieval trials conducted without a list, suggesting that the list may have served a mediating function during retrieval. Transfer of stimulus control of computer-based teaching to the retrieval task may have been attributable to the existence of stimulus classes involving pictures, objects, and printed words. Reprinted by permission of the publisher.